Influence of flight-path variability of conditions upon in-flight icing - Stanfield, Robin (Cranfield University, 2008)
In design and development of aircraft, standard practice uses `the icing design envelopes' to select atmospheric conditions for modelling icing encounters. Over the duration of these encounters, atmospheric conditions are assumed to be constant and to exhibit no variability. In reality variability exists, to an extent where it may adversely affect the severity of ice accretions beyond that identified by ground-based modelling. Similarly, certain tools and systems employed by industry may sacrifice efficiency & effectiveness in neglecting the variability that exists. This project considered what operational and safety bene ts might be derived from an enhanced knowledge of ice accretion under more realistic, variable conditions; in contrast with a reference case identified to have equivalent constant conditions. In doing so, variable encounters were modelled experimentally in an icing tunnel to compare against a constant-condition reference; aerodynamic penalty was assessed numerically using CFD, allowing a comparison to be made between variable and constant-condition profiles; and desk-research considered variable conditions in the context of existing and emerging technology. Considerable differences were observed between variable profiles themselves and with the reference profile, with aerodynamic penalty being considerably enhanced for 25% of variable cases, and considerably reduced for a further 25%. Desk-research suggests that in understanding variability, to reduce costs asso- iciated with aircraft icing, more realistic ground-based modelling capabilities could reduce the need for natural flight-testing in the long term, though this would require substantial enhancement to current numerical prediction capabilities. Similarly, the power applied to ice protection systems could be tailored more speci cally to demand, enhancing e ciency. On the basis of current instrumentation, this would first require development of more accurate and robust LWC measurement systems. It was therefore recommended that specialists in meteorology, icing physics, ice protection systems and aerodynamics; conduct more extensive research towards understanding variability and assessing its potential to enhance flight-safety, whilst simultaneously reducing cost.